PENDIDIKAN KESEHATAN NUTRISI IBU HAMIL DENGAN INOVASI PENGOLAHAN KROYAM (KROKET, KENTANG, AYAM, WORTEL, BAYAM,). - Sri Untari; Rizki Sahara; Nurya Kumalasari; Nur Fatimah; Nurul kodiyah; Dhiyan Nany Wigati; Meity Mulya Susanti; Riska Indriyati (LPPM AN Nuur, 2025)
Background: Nutrition is the intake of nutrients from food and drinks that support health and cell development. For pregnant women, proper nutrition is crucial for both maternal health and fetal growth. However, their knowledge about pregnancy nutrition needs improvement. This community service activity aims to increase pregnant women's awareness of proper nutrition and introduce nutritious local foods like Kroyam (croquettes made from potato, chicken, carrot, and spinach) and orange juice. Methods : included health counseling on nutrition for pregnant women, accompanied by demonstrations on healthy food preparation. Evaluation was conducted through pre-tests before counseling and post-tests after counseling. This activity was carried out at the Pilang Payung Village Hall, Toroh District, Grobogan Regency, with 18 pregnant women participating. Results: From the counseling session, it was found that 18 pregnant women experienced an increase in the knowledge category, namely 18 respondents (100%). Conclusion: Through the implementation of the